Experimental vertical jump model used to evaluate the pivot location in klap speed skates - Allinger, T. L.; Motl, R. W. (Journal of Applied Biomechanics, 2000)
This study used a vertical jump model to simulate the push-off phase for a skater using klap speed skates and evaluated die effects of pivot location and shoe base flexion on energy production. Boards of different lengths and one board with a hinge under the metatarsal heads were attached to the running shoes of volunteers. Six skaters performed 3 maximal effort vertical jumps across 5 different base conditions: running shoe, board that hinged under metatarsal heads, and rigid boards that pivoted with the ground al -25 mm (typical pivot location for klapskales), 0 mm, and +25 mm from the toes. There were no significant differences in total energy at take-off among the 3 rigid base conditions, but there were differences in potential and kinetic energy production. The total and kinetic energy produced at take-off was 9% greater in the hinged base condition than the corresponding rigid base condition. If differences in energy measures from the vertical jump reflect those for skating, a hinged boot base could increase skating speeds by about 3% over the current klap-skales, which have a rigid boot base.